Ecological notes and occurrence of Astrangia solitaria (Le Sueur, 1817) (Cnidaria: Astrangiidae) for the Northern Brazilian Coast - Alves-Júnior, Flavio Almeida; Galvão, Déborah Elena Martins; Silva, Kátia Cristina Araújo; Klautau, Alex Garcia Cavalleiro de Macedo; Cintra, Israel Hidenburgo Aniceto (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
Ecological associations are widely reported in literature, covering several levels in the trophic chain or with different species interaction. However, the epibiosis between coral and gastropod species is still rarely observed in Brazil. Therefore, herein we report the epibiosis between the coral species Astrangia solitaria (Le Sueur, 1817) and the gastropod Turbinella laevigata Anton, 1838, additionally, extending the distribution of A. solitaria from the northern Brazilian coast (State of Amapá). The species were collected as bycatch fauna during commercial fishing operations along the continental shelf of Amapá, under the supervision of Center for Research and Management of Fisheries Resources of the North Coast (CEPNOR). This paper increases the northernmost record of A. solitaria and expands its epibiosis interaction with T. laevigata.
Keywords: Epibiosis; Coral; Mesophotic reefs; Gastropod mollusk; State of Amapá